Two Heroines – One Destiny: a Comparative Analysis of the Images of Anna Karenina and Emma Bovary (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the comparative analysis of the images of Anna Karenina and Emma Bovary. The main goal is